Glokalisasi: Membangun Pendidikan Global Berbasis Kearifan Lokal Pada Pondok Modern - Khoirul Mudawinun Nisa' (LP2M Sekolah Tinggi Agama Islam (STAI) Madiun, 2018)
To meet the era of changing world economic order, education must have global competence and accommodate local wisdom based on local culture that has productive economic potential. This article, in a qualitative research that aims toâ€œPromote inclusive and equitable quality education and promote lifelong learning opportunities for all based on glocalizationâ€. Collected by observations, interviews and documentations, it is concluded that in the learning process integrates the values of GED (The Glocal Engagement Dimensions) to learning materials. The four dimensions of the GED are : 1) Intellectual knowledge education wisdom; 2) Emotion sensitivy intuition understanding compassion; 3)Action decisive, action driven resolution oriented; 4) Morality integrity virtue fairness. Each of the four dimensions has a significant role to relize equitable, inclusive, and diversityfocused in modern Cottage education framework.